EVALUATION OF PETROLEUM PRODUCTS MARKETING IN A GLOBALIZING ECONOMY: A CONCEPTUAL EVIDENCE FROM NIGERIA - Isaac Oladepo, ONIGBINDE (British Journal of Marketing Studies, 2014)
The downstream sector of the Nigeria’s petroleum industry is a key sector in the country’s economy having four refineries with a nameplate capacity of 445,000 barrel per day, more than eight (8) major and over three hundred and fifty (350) independent petroleum products’ marketers, all active in marketing, distribution and retailing of petroleum products in the country. The state-owned Nigerian National Petroleum Corporation (NNPC) has had an all-encompassing control over the Nigeria’s petroleum industry, while the Petroleum Product Pricing Regulatory Agency (PPPRA) is involved in fixing and regulation of wholesale and retail prices of petroleum products across the country. Consequent upon this, Nigerians have experienced several decades of shortages of refined petroleum products and this has led to increased imports to meet the domestic demand. Nigeria’s petroleum industry has experienced enormous problems such as poor management and lack of turnaround maintenance resulting in the refineries operating below full capacity. The PPPRA, the NNPC and other stakeholders in the downstream sector of the Nigeria’s petroleum industry are to take all necessary measures to sustain the current petroleum products supply stability in the system, while there should be adherence to approved official pump prices ceiling by petroleum products marketers